PEMBELAJARAN MATERI GERAK TARI TRADISIONAL MELALUI METODE DEMONSTRASI DI KELAS VIIISMP NEGERI 1 KABILA BONE - Safina Fitra Amalia Ohi; Riana Diah Sitharesmi; Rahmawati Ohi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to describe the learning process of traditional dance movement material, particularly the Tidi Lo O’Ayabu dance, through the demonstration method among Grade VIII students of SMP Negeri 1 Kabila Bone. The background of this study is the ineffectiveness of previous dance learning processes that relied solely on audio-visual media, resulting in many students experiencing difficulties in applying practical material and failing to achieve the Minimum Mastery Criteria (KKM). This study employed a descriptive qualitative approach. Data were collected through direct observation, unstructured interviews with the school principal, cultural arts teachers, and students, as well as documentation. The research subjects consisted of all Grade VIII students of SMP Negeri 1 Kabila Bone. The learning steps were organized into nine meetings, including theory delivery, visual observation, and direct practice through the demonstration method in which the teacher acted as a model. The results showed that the implementation of the demonstration method significantly improved students’ psychomotor skills, cognitive understanding, and affective attitudes. Students became more enthusiastic, were able to understand complex movement details more easily, and were capable of performing the Tidi Lo O’Ayabu dance in groups with assessment categories ranging from “Good” to “Very Good.” Through this method, students not only memorized movements but also understood their philosophical meanings and contributed to the preservation of Gorontalo’s local cultural heritage.